Analisis Pengaruh Sarana Prasarana dan Kinerja Pegawai terhadap Kepuasan Pemohon Layanan Publik di Kantor Imigrasi Jakarta Barat - Muh. Syeh Yusuf; Pascalis Danny Kristi Wibowo; Anida Sri Rahayu Mastur (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Quality public services require adequate infrastructure and optimal employee performance. The West Jakarta Immigration Office, as a public service provider, is obligated to address the needs of the community in accordance with its duties and functions. This research will examine the contribution of infrastructure and civil servant performance to public satisfaction with public services at the West Jakarta Immigration Office. Qualitative research using a direct survey was the method of choice. The sample was determined using the Slovin formula, and data were obtained from pre-processed questionnaires. A t-test in multiple linear analysis was performed, along with the coefficient of determination and f-test. The results showed that satisfaction was significantly and positively influenced by infrastructure, as was employee performance. Both variables contributed strongly to public service satisfaction. In conclusion, improving infrastructure quality and optimizing employee performance are important factors in creating satisfaction with complaints at the West Jakarta Immigration Office. This research is expected to contribute to enriching the public sector service literature, particularly regarding infrastructure, human resources, and service quality. Practically, these findings can provide input for the leadership of the West Jakarta Immigration Office in formulating policies that focus on infrastructure investment and employee capacity development. In this way, it is hoped that more efficient, transparent and accountable services can be achieved, in line with public demands for good and responsive governance.